Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300897
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Understanding Photo Sharing Experiences in Social Virtual Reality

Abstract: Millions of photos are shared online daily, but the richness of interaction compared with face-to-face (F2F) sharing is still missing. While this may change with social Virtual Reality (socialVR), we still lack tools to measure such immersive and interactive experiences. In this paper, we investigate photo sharing experiences in immersive environments, focusing on socialVR. Running context mapping (N=10), an expert creative session (N=6), and an online experience clustering questionnaire (N=20), we develop and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 60 publications
2
69
2
Order By: Relevance
“…This can realize realistic social participation and improve safety. Moreover, Jie Li et al compared the photo sharing experience under social VR with Skype and Facebook spaces, and found that social VR was closer to face-to-face (F2F) sharing [32,35]. Baker et al [36] studied 22 elderly individuals to obtain their views on social VR in the form of a workshop, and suggested that social VR virtual items could trigger memories that could be shared with others, meeting their social needs [33].…”
Section: Advantages Of Vr Technology In Social Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This can realize realistic social participation and improve safety. Moreover, Jie Li et al compared the photo sharing experience under social VR with Skype and Facebook spaces, and found that social VR was closer to face-to-face (F2F) sharing [32,35]. Baker et al [36] studied 22 elderly individuals to obtain their views on social VR in the form of a workshop, and suggested that social VR virtual items could trigger memories that could be shared with others, meeting their social needs [33].…”
Section: Advantages Of Vr Technology In Social Developmentmentioning
confidence: 99%
“…(1) Most of the current literature on social VR is aimed at the young, with few designed for the needs of the elderly [35,42,43]. (2) In addition, studies on the elderly centers on the design of the virtual avatar [36], with no comprehensive consideration of multiple dimensions and variable factors, and no guidance based on them.…”
Section: Gaps In Previous Studiesmentioning
confidence: 99%
“…As an augmentation, social VR provides many benefits. First, it immerses the users in the same virtual world, providing realistic and co-presence experience [19]. Second, it uses virtual representations to offer embodiment experiences to users, and abilities to interact with the virtual environment and artifacts [13].…”
Section: Discussionmentioning
confidence: 99%
“…Second, it uses virtual representations to offer embodiment experiences to users, and abilities to interact with the virtual environment and artifacts [13]. Third, it enables the sense of social connectedness [19] and allows people to see and feel from other person's perspective [31].…”
Section: Discussionmentioning
confidence: 99%
“…The users' audio and visual interactions, including the HMD viewports for the sVR sessions, and recordings of their body movements, are captured. After testing each system, users are asked to fill in a questionnaire designed for the purpose of our test based on an adaptation of the questionnaire described and evaluated at [5]. The questionnaire focuses on three main factors: the quality of interaction, the social connectedness, and the sense of presence/immersion experienced by the users.…”
Section: Methodsmentioning
confidence: 99%